2010
DOI: 10.2223/jped.1999
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of accidental extubation in a neonatal intensive care unit

Abstract: Objective:To determine the incidence and risk factors of accidental extubation (AE) in a tertiary neonatal intensive care unit.Methods: A prospective cohort study was conducted to determine AE incidence density per 100 patient-days, during a 23-month period, in 222 newborns receiving assisted ventilation (AV). Logistic regression analysis was used to determine risk factors for AE. The presence of a cyclical pattern in extubation rates, according to the variables of interest, was investigated by Cosinor analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 27 publications
4
31
0
4
Order By: Relevance
“…Veldman et al 13 descobriram que o número médio de recém-nascidos por enfermeiro durante turnos em que ocorreram EAIs era maior do que a média observada durante o período de estudo. Finalmente, Carvalho et al 14 sugeriram que o risco de EAIs era provavelmente determinado pela maior necessidade de cuidados de enfermagem.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Veldman et al 13 descobriram que o número médio de recém-nascidos por enfermeiro durante turnos em que ocorreram EAIs era maior do que a média observada durante o período de estudo. Finalmente, Carvalho et al 14 sugeriram que o risco de EAIs era provavelmente determinado pela maior necessidade de cuidados de enfermagem.…”
Section: Discussionunclassified
“…Essa carga de trabalho era maior do que a média de 3 recém-nascidos por enfermeiro (variação: 1,6-6,0 recém-nascidos por enfermeiro) observada durante o período de estudo. Em um estudo de coorte prospectiva, Carvalho et al 14 demonstraram que, quanto maior o número de pacientes-dia ventilados, maior o risco de extubação artificial, e que isso foi provavelmente determinado pela maior necessidade de cuidados de enfermagem, ultrapassando a capacidade do serviço.…”
Section: Introductionunclassified
“…Carvalho et al (11) reported that the mean accidental extubation density was 5.34/100 patient-days on MV in a tertiary neonatal ICU, and that the duration of assisted ventilation was its only independent predictor. The authors also stated that the best accuracy for the occurrence of accidental extubation was achieved at 10.5 days of assisted ventilation.…”
Section: Diagnostic Proceduresmentioning
confidence: 99%
“…One such adverse event is accidental extubation (AE). This aspect of neonatal intensive care was evaluated in an article by Carvalho et al 2 in this issue of Jornal de Pediatria. AE in neonates has been reported to vary from 0.72 to 4.8/100 intubated days.…”
mentioning
confidence: 99%
“…AE in neonates has been reported to vary from 0.72 to 4.8/100 intubated days. 2 The prospective cohort study, conducted over almost 2 years, had an AE rate of 5.34/100 intubated days. The unit routinely practiced nasal intubation and while on mechanical ventilation also used analgesia (with fentanyl), and if necessary, sedation with midazolam.…”
mentioning
confidence: 99%